2013
DOI: 10.5539/apr.v5n1p51
|View full text |Cite
|
Sign up to set email alerts
|

Absorption Coefficient of Molten Aluminum Oxide in Semitransparent Spectral Range

Abstract: A critical compilation and analysis of all the available experimental data and approximation formulas for the wavelength and temperature dependences of the absorption coefficient of molten aluminum oxide in semitransparent region are presented. The main factors and the influence of physicochemical processes on the value of the absorption coefficient are considered. Special attention is focused on possible reasons for large values of absorption of the alumina melt as compared to the crystal near melting tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…The temperature measurements for sapphire were carried out with high spatial resolution. Therefore we can argue that the temperature profile doesn't contain singularities in transition area between the melt and solid crystal despite the fact that the absorption coefficient demonstrates sharp increase of the two orders in magnitude in melting process [14,17].…”
Section: Resultsmentioning
confidence: 97%
“…The temperature measurements for sapphire were carried out with high spatial resolution. Therefore we can argue that the temperature profile doesn't contain singularities in transition area between the melt and solid crystal despite the fact that the absorption coefficient demonstrates sharp increase of the two orders in magnitude in melting process [14,17].…”
Section: Resultsmentioning
confidence: 97%
“…The first of all is the uncertainty on the spectral and temperature dependence of alumina absorption index which may strongly influence the radiation calculation. Indeed, the absorption index has been proven to strongly depend on the impurities present in the combustion produced alumina [14]. Secondly, the uncertainty and approximations made on the nozzle exit conditions would also play an important role on the results.…”
Section: Simulation Results and Comparisonsmentioning
confidence: 99%
“…Considering that the size of particules in our application is about a few micrometers, Mie theory [13] is used to calculate these radiative properties. Many investigations have been made in the past decades in order to find expressions of the refractive index n and the absorption index k as functions of the temperature and the wavelength [14,15] . Strong discrepancies exist between those studies as the results for k may vary by several orders of magnitude depending on the temperature and wavelength range of the studies and the type of investigated alumina (liquid phase or crystalline phase of solid alumina).…”
Section: Radiative Properties Of Alumina Particlesmentioning
confidence: 99%
“…Although -values are reported by Lawrence (2004) and Bityukov and Petrov (2013), variations can extend over several orders of magnitude. Alumina shows low absorption of Yb:YAG laser light, and it can be strongly modified by impurities.…”
Section: Volumetric Heat Source Parametersmentioning
confidence: 91%
“…Even though literature values for absorption coefficients are scarce and show a large scatter for Al 2 O 3 , the identified values are relatively close. The review conducted by Bityukov and Petrov (2013) showed that values vary from 1 mm -1 at the melting point to 60 mm -1 at boiling point for pure powders, and from 20 mm -1 to 90 mm -1 for impure powders. The value for the dense material at room temperature reported by Sola and Peña (2013) was 1 mm -1 .…”
Section: Second Identification With the Numerical Modelmentioning
confidence: 99%